A comprehensive spatiotemporal and risk reduction drought assessment study utilizing SPEI index for Urmia Lake Basin, Iran - Sadaf Samiei; Mohammadali Alijanian (Journal of Hydrology: Regional Studies)
Study Region: The Urmia Lake Basin (ULB) in northwestern Iran, a region highly susceptible to drought. Study Focus: Effective drought risk reduction necessitates comprehensive spatiotemporal assessment. The ULB has experienced a severe, near two-decade-long drought resulting in a 90 % reduction in lake area. This situation has fueled debate between attributing the crisis to governance failures and emphasizing the role of drought. Hence, this study performs a comprehensive drought assessment, considering temporal, spatial, and risk reduction aspects. Using a 50-year (1971–2020) time series of multivariate Standardized Precipitation-Evapotranspiration Index (SPEI) data (3, 6, 9, and 12-month timescales), the study employs Mann-Kendall, modified Mann-Kendall, and Sen's slope analyses to determine drought trends, examines spatial patterns using Severity Area Frequency (SAF) curves, and finally, evaluates drought risk reduction using resilience, vulnerability, and exposure factors. New Hydrological Insights for the Region: the study reveals a significant decreasing trend in SPEI values across the basin, particularly pronounced in the southern region, indicating worsening drought conditions. Regional drought assessment identified 1998 as the most severe drought event, exhibiting a 50-year return period basin-wide. Finally, risk assessment based on drought mitigation indicators shows the highest short-term and mid-term (SPEI3 and SPEI9) drought risk in the southern region. However, for long-term droughts (SPEI12), the eastern region displays the highest risk, while the southern region shows at the lower rank.